THE FORMATION OF SYMBOL AND ALLEGORY IN EASTERN POETICS (Universal International Scientific Journal, 2026)
This paper explores the stages of formation of symbol and allegory in Eastern poeticsand examines their aesthetic and poetic functions. Drawing on examples from ancient Indian, PersianTurkic, and Islamic literary traditions, the study analyzes the development of symbol and allegory asartistic devices conveying moral, philosophical, religious, and social meanings. Special attention isgiven to the role of symbolism in Jadid literature and in Uzbek literature of the independence period asa means of social criticism, national consciousness, and philosophical reflection
Keywords: Eastern poetics; symbol; allegory